2017
DOI: 10.1111/imm.12766
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐bound Dickkopf‐1 in Foxp3+ regulatory T cells suppresses T‐cell‐mediated autoimmune colitis

Abstract: SummaryInduction of tolerance is a key mechanism to maintain or to restore immunological homeostasis. Here we show that Foxp3+ regulatory T (Treg) cells use Dickkopf‐1 (DKK‐1) to regulate T‐cell‐mediated tolerance in the T‐cell‐mediated autoimmune colitis model. Treg cells from DKK‐1 hypomorphic doubleridge mice failed to control CD4+ T‐cell proliferation, resulting in CD4 T‐cell‐mediated autoimmune colitis. Thymus‐derived Treg cells showed a robust expression of DKK‐1 but not in naive or effector CD4 T cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…2 inflammation (33). Recently, it was demonstrated that Dkk-1 is uniquely expressed in Foxp3 + Treg cells to inhibit T-cell-mediated autoimmune colitis as a membrane-bound form (34). However, despite the eminent role of osteocyte derived Dkk-1 on inflammation, the exact mechanism of the immunomodulatory property of Dkk-1 deserves further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…2 inflammation (33). Recently, it was demonstrated that Dkk-1 is uniquely expressed in Foxp3 + Treg cells to inhibit T-cell-mediated autoimmune colitis as a membrane-bound form (34). However, despite the eminent role of osteocyte derived Dkk-1 on inflammation, the exact mechanism of the immunomodulatory property of Dkk-1 deserves further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Whether DKK-3 could modulate Wnt signaling was not addressed in this study. For DKK-1, the expression of this protein in regulatory T cells was demonstrated in a murine IBD model with a lymphopenic environment, suggesting that DKK-1 harbors an immunosuppressive role in Tregs, and prevents CD4 + T cell proliferation [92]. The study also showed that DKK-1 expression was independent of Wnt pathway activation.…”
Section: Wnt Antagonists and Inflammatory Diseases Dkk Family Membersmentioning
confidence: 76%
“…However, another study showed that at least canonical Wnt signaling had a negative effect on Treg function (53). The positive association of membrane-bound DKK-1, a Wnt antagonist, and the suppressive function of Tregs confirmed this observation (54). Analyzing the proportion of CD25 + /Foxp3 + Tregs among the CD4 + effector T cells, we did not detect any effect of either Wnt-1 or Wnt-5a in the lung or draining lymph node, consistent with our transgenic assay data.…”
Section: Discussionmentioning
confidence: 87%